A review on the development of catering service and demand in foodservice organization / Adam Abdullah Abdul Manaf and Nurul Aliah Safwah Md Fadzil - Abdul Manaf, Adam Abdullah; Md Fadzil, Nurul Aliah Safwah (2017)
Foodservice plays an important role and specifically in Malaysian due to tourism development and the phenomenon of Malaysians eating out (Euromonitor, 2006). According to (Samoggia, Bertazzoli, Hendrixson, Glibetic, and Arvola, 2016) higher income of persons especially women will influence the factors of perceived behavioral control, attitudes towards healthy eating, subjective norms and level of knowledge regarding healthy food. They also will related with family habits and food affordability and availability. Apart from that, it was found that, due to busy schedules in the city and income increases of Malaysian household, many of them preferred to dine out instead of cooking and eating at home (McCluskey, 2015). This was seen one of the main drivers that constantly push the foodservice industry and give positive impact on the national economy.